(untitled) (Research, Society and Development, 2021)
The Material and Sterilization Centers (CME) is a unit with high technological demand that must adjust to sustainable development practices. Objective: Analyze scientific production on sustainability practices in the scenario of the CME. Method: Integrative literature review, systematized by the acronym Participant, Interest and Context (PICo) according to the strategy (PICo) and methodological procedures defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Databases consulted: Online System for Searching and Analyzing Medical Literature (MEDLINE) / PubMed, Latin American and Caribbean Literature in Health Sciences (Lilacs) and Base Nursing Data (BDEnf) from the Virtual Health Library (VHL), Scopus (Elsevier) from the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES). Search carried out from April to June 2021. Publications from 2012 to 2020 were considered, in Portuguese, English and Spanish. Eight studies were selected for analysis. Results: Predominant descriptive studies (42.8%) and brazilians (85.7%) published in the period 2013 to 2020. Conclusion: The sustainability practices at CME include the review of processing practices to avoid excessive consumption of water and electricity. In the waste chain, CME participates in the generation, segregation and treatment of infectious waste. Highlight for the work of the professional Nurse who plays a fundamental role in environmental sustainability, not only in the management of health systems, but also in assistance.